2021
DOI: 10.1093/gbe/evab135
|View full text |Cite
|
Sign up to set email alerts
|

Transposable Elements Contribute to Genome Dynamics and Gene Expression Variation in the Fungal Plant PathogenVerticillium dahliae

Abstract: Transposable elements (TEs) are a major source of genetic and regulatory variation in their host genome and are consequently thought to play important roles in evolution. Many fungal and oomycete plant pathogens have evolved dynamic and TE-rich genomic regions containing genes that are implicated in host colonization and adaptation. TEs embedded in these regions have typically been thought to accelerate the evolution of these genomic compartments, but little is known about their dynamics in strains that harbor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 182 publications
(327 reference statements)
4
39
0
Order By: Relevance
“…3d ). This observation would corroborate the hypothesis of stress-driven TE de-repression observed in other patho-systems 43 45 . However, it also shows that in P. pachyrhizi only a small percentage of the TEs are highly expressed during early infection stages.…”
Section: Resultssupporting
confidence: 89%
“…3d ). This observation would corroborate the hypothesis of stress-driven TE de-repression observed in other patho-systems 43 45 . However, it also shows that in P. pachyrhizi only a small percentage of the TEs are highly expressed during early infection stages.…”
Section: Resultssupporting
confidence: 89%
“…A study by Wyka et al (2021) investigated the plant pathogen Claviceps and found that expansion of transposable elements and tandem gene duplications coincided with increased host range potential and speciation. According to Wyka et al, this indicates that “alterations of genomic architecture and plasticity can substantially influence and shape the evolutionary trajectory of fungal pathogens and their adaptability.” Consistent with this, Torres et al (2021) identified polymorphic transposable elements in the fungal plant pathogen Verticillium dahliae that colocalized near pathogenicity-related genes and correlated with high expression levels, suggesting that these elements may impact the evolution of adaptive genomic regions.…”
supporting
confidence: 61%
“…These damaging effects can be avoided and controlled by epigenetic silencing, such as through DNA methylation [193]. siRNAs are interconnected with various TEs and act as mediators and stimulate DNA methylation [252]. This DNA methylation may lead to suppression of transposition through transcription reduction, along with the formation of loops among DNA and histone methylations (Figure 4) through siRNAs [253].…”
Section: Te Methylationmentioning
confidence: 99%